Perlindungan Hukum Terhadap Pemenang Lelang Hak Tanggungan Dalam Proses Peralihan Hak Atas Tanah Karena Lelang - Andriansa Buana, Erlando; Sungkowo Raharjo, Purwono (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This legal research aims to find out how the form of legal protection given by mortgage regulations to the auction winner in the transfer of land rights and what obstacles occur in the transfer of land rights to the auction winner at the Sukoharjo Regency Land Office. This research is normative legal research which is prescriptive. The research approach used is a statutory approach. Types of legal materials used are primary legal materials and secondary legal materials. The type of data used is literature study and clarification. Furthermore, using analysis techniques that are deductive. The results of the study indicate that the legal protection given by mortgage regulations to the winner of the auction in carrying out the transfer of land rights that he has won. While the obstacles that occur to the auction winner in carrying out the transfer of land rights; the existence of a lawsuit proposed by the former debtor as the original land owner, the blocking of land against the auction object that has been won, and the former debtor as the original land owner was not immediately to vacate the auction object that should have rotated to another party. This study is carried out so that the auction winner gets the right that should be obtained for the purchase of the auction object he has won.